How culture influences perspective taking: differences in correction, not integration - Wu, Shali; Barr, Dale J.; Gann, Timothy M.; Keysar, Boaz (Frontiers in Human Neuroscience, 2013)
Individuals from East Asian (Chinese) backgrounds have been shown to exhibit greater sensitivity to a speaker's perspective than Western (US) participants when resolving referentially ambiguous expressions. We show that this cultural difference does not reflect better integration of social information during language processing, but rather is the result of differential correction: in the earliest moments of referential processing, Chinese participants showed equivalent egocentric interference to Westerners, but managed to suppress the interference earlier and more effectively. A time-series analysis of visual-world eyetracking data found that the two cultural groups diverged extremely late in processing, between 600-1400 ms after the onset of egocentric interference. We suggest that the early moments of referential processing reflect the operation of a universal stratum of processing that provides rapid ambiguity resolution at the cost of accuracy and flexibility. Late components, in contrast, reflect the mapping of outputs from referential processes to decision-making and action planning systems, allowing for a flexibility in responding that is molded by culturally specific demands.